1987
DOI: 10.1063/1.452374
|View full text |Cite
|
Sign up to set email alerts
|

CARS spectroscopy of O2(1Δg) from the Hartley band photodissociation of O3: Dynamics of the dissociation

Abstract: Rotationally and vibrationally resolved CARS spectra of the O2(1Δg) photofragment produced by the photodissociation of O3 at 17 wavelengths between 230 and 311 nm are reported. The spectra are taken under collision-free conditions, therefore, they reveal the nascent rotational and vibrational state distributions of the O2(1Δg) photofragment. At all photolysis wavelengths studied the vibrational distribution peaks very sharply at v=0, although all energetically allowed vibrational states are observed. The rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 16 publications
9
87
1
Order By: Relevance
“…The vibrational state distribution-is thus determined by Franck-Condon factors at the crossing seam. The branching fraction obtained is 16% for this channel, slightly higher than reported elsewhere in the Hartley band, [11,12] but consistent with a nonadiabatic transition coupled with a higher velocity through the crossing region.…”
Section: Channellmentioning
confidence: 71%
See 3 more Smart Citations
“…The vibrational state distribution-is thus determined by Franck-Condon factors at the crossing seam. The branching fraction obtained is 16% for this channel, slightly higher than reported elsewhere in the Hartley band, [11,12] but consistent with a nonadiabatic transition coupled with a higher velocity through the crossing region.…”
Section: Channellmentioning
confidence: 71%
“…The dominant photochemical events there are fairly well understood as a result of several molecular beam experiments, [10,11] an extensive series of CARS experiments performed by Valentini and coworkers, [12], and resonance Raman experiments by Kinsey and others. [13,14] It is known that, in the Hartley band, the initially prepared "B" state (1 B 2 in C 2 v, iJ in Cs) correlates to singlet products, so these dominate (85-90%).…”
Section: Lawrence Berkeley Laboratorymentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the quantum yield of the singlet channel to 100% and decreasing it to 80% was found to have no significant effect on the model-calculated isotopic compositions. Valentini et al, [1987] showed that the UV photolysis of 03 can produce mass independently enriched 02 through an isotopically selective curve crossing from the singlet surface to the triplet surface. This effect is not relevant to the present study because the process does not influence which 03 bond is broken, only whether the photolysis leads to singlet or triplet products.…”
Section: Photochemical Box Modelmentioning
confidence: 99%